S-Adenosyl-L-Methionine Augmentation in Patients with Stage II Treatment-Resistant Major Depressive Disorder: An Open Label, Fixed Dose, Single-Blind Study - Domenico De Berardis; Stefano Marini; Nicola Serroni; Gabriella Rapini; Felice Iasevoli; Alessandro Valchera; Maria Signorelli; Eugenio Aguglia; Giampaolo Perna; Anatolia Salone; Giuseppe Di Iorio; Giovanni Martinotti; et al. (The Scientific World Journal)
We investigated the efficacy of S-Adenosyl-L-Methionine (SAMe) augmentation in patients with treatment-resistant depressive disorder (TRD). Thirty-three outpatients with major depressive episode who failed to respond to at least 8 weeks of treatment with two adequate and stable doses of antidepressants were treated openly with fixed dose of SAMe (800 mg) for 8 weeks, added to existing medication. The primary outcome measure was the change from baseline in total score on Hamilton Rating Scale for Depression (HAM-D). The Clinical Global Impression of Improvement (CGI-I) was rated at the endpoint. Patients with a reduction of 50% or more on HAM-D total score and a CGI-I score of 1 or 2 at endpoint were considered responders; remission was defined as a HAM-D score ≤7. Secondary outcome measures included the Snaith-Hamilton Pleasure Scale (SHAPS) and the Sheehan Disability Scale (SDS). At 8 weeks, a significant decrease in HAM-D score was observed with response achieved by 60% of the patients and remission by 36%. Also a statistically significant reduction in SHAPS and SDS was observed. Our findings indicate that SAMe augmentation may be effective and well tolerated in stage II TRD. However, limitations of the present study must be considered and further placebo-controlled trials are needed.